42‐1: A Promising Strategy of Low‐Power Circuit Design for Integrated Display Driver Using Charge‐Trap Memory and Oxide Thin Film Transistors. Issue 1 (30th May 2018) - Byun, Chun-Won; Kim, Yeo-Myeong; Yu, Byung-Chang; Yang, Jong-Heon; Hwang, Chi-Sun; Kim, So-Jung; Lee, Seung-Hyuck; Lee, Seung-Woo; Cho, Nam Sung; Lee, Jeong-IK; Yoon, Sung-Min
Abstract : We propose the design concept for dramatically reducing the power consumption of integrated circuit using TFTs, which is named as Read‐out Modulation (RoM). In the RoM scheme, the read‐out voltages applied to the charge‐trap memory TFTs are intentionally modulated to replace the clocks of shift registers to minimize the clocking power consumption. The test circuit is fabricated and the proposed RoM is successfully verified with the frequency characteristics.